ГІПОТЕЗА ìОРГАНІЧНОСТІ ГЛОБАЛЬНИХ ВІЙН В ІНДУСТРІАЛЬНОМУ СУСПІЛЬСТВІî ІМПЕРСЬКОГО НАПРЯМКУ (Zaporizhzhia Historical Review, 2021)
In the article the history of the creation of the hypothesis ìglobal warsí organity in the imperial industrial communityî is regarded. Its genetic connection with the previous scientific hypothesis is found out, the key phenomena are ascertained and revealed, its consequences are determined.